Determining the Prevalence of Patent Parasite Infections in Raccoons from West-Central Illinois - Mitchell, Mark; Hungerford, Laura; Nixon, Charles; Esker, Terry; Sullivan, Joseph; Koerkenmeier, Robert (Wildlife Rehabilitation Bulletin, 2004)
The raccoon (Procyon lotor) is an omnivorous mammal that is widely distributed throughout North America (Kaufman 1982). This omnivorous diet exposes the raccoon to a broad spectrum of intestinal parasites. Because the raccoon is highly adapted to both urban and rural environments, and raccoon densities are increasing in both types of areas (Hoffman and Gottschang 1977), there is increased contact between humans and raccoons. Greater contact with raccoons creates a potential for human and domestic animal exposure to parasites normally harbored by raccoons. Intestinal parasitism can cause serious consequences for the vertebrate host, including weight loss, poor pelt, anemia, and death (Hanson 1933; Soulsby 1982). Intestinal parasitism in the raccoon has been studied extensively, especially in the Midwest and Southeast (Cole and Shoop 1987; Schaffer et al. 1981; Smith et al. 1985; Snyder and Fitzgerald 1985a). Several studies in different geographic locations have characterized age, gender, season, and/or location patterns for Baylisascaris procyonis (Kidder et al. 1989; Snyder and Fitzgerald 1985b); however, no study has evaluated the combination of these factors for B. procyonis and/or other intestinal parasites simultaneously. The objectives of this study were to (1) determine the prevalence of patent intestinal nematode and protozoal infections in raccoons; (2) compare prevalence of shedding between age and gender groups; and (3) compare prevalence of shedding between raccoons captured in different sites or seasons.